The Effectiveness of the Environmental Care and Culture Movement in Schools (GPBLHS) Program on Junior High School Students’ Environmental Awareness - Harmedi Yulian Saputra; Nurhasan Syah; Aulia Azhar; Ratna Wilis (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effectiveness of the Environmental Care and Culture Movement in Schools (GPBLHS) program in developing environmental attitudes among junior high school students by comparing Adiwiyata and non-Adiwiyata schools in Padang City. This research employed a quantitative ex post facto approach with 120 students as research participants, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using the Mann-Whitney U-Test due to the non-normal distribution of the data. The results show a significant difference in students’ environmental attitudes between Adiwiyata and non-Adiwiyata schools, with a significant value of 0.000 (p < 0.05). Students in Adiwiyata schools demonstrated higher attitudes, indicated by a mean rank of 88.05, compared to 32.95 in non-Adiwiyata schools. Additionally, the percentage of environmental attitude indicators in Adiwiyata schools ranged from 71.5% to 77.3% (high category), while those in non-Adiwiyata schools ranged from 36.4% to 41.2% (low to moderate category). These findings indicate that the GPBLHS program is effective in cultivating environmental attitudes and environmentally responsible behavior among students.